Efficacy of a Russian-backbone live attenuated influenza vaccine among young children in Bangladesh: a randomised, double-blind, placebo-controlled trial. Issue 12 (December 2016) - Brooks, W Abdullah; Zaman, K; Lewis, Kristen D C; Ortiz, Justin R; Goswami, Doli; Feser, Jodi; Sharmeen, Amina Tahia; Nahar, Kamrun; Rahman, Mustafizur; Rahman, Mohammed Ziaur; Barin, Burc; Yunus, Muhammad; et al.
Summary: Background: The rates of influenza illness and associated complications are high among children in Bangladesh. We assessed the clinical efficacy and safety of a Russian-backbone live attenuated influenza vaccine (LAIV) at two field sites in Bangladesh. Methods: Between Feb 27 and April 9, 2013, children aged 2–4 years in urban Kamalapur and rural Matlab, Bangladesh, were randomly assigned in a 2:1 ratio, according to a computer-generated schedule, to receive one intranasal dose of LAIV or placebo. After vaccination, we monitored children in weekly home visits until Dec 31, 2013, with study clinic surveillance for influenza illness. The primary outcome was symptomatic, laboratory-confirmed influenza illness due to vaccine-matched strains. Analysis was per protocol. The trial is registered withClinicalTrials.gov, numberNCT01797029 . Findings: Of 1761 children enrolled, 1174 received LAIV and 587 received placebo. Laboratory-confirmed influenza illness due to vaccine-matched strains was seen in 93 (15·8%) children in the placebo group and 79 (6·7%) in the LAIV group. Vaccine efficacy of LAIV for vaccine-matched strains was 57·5% (95% CI 43·6–68·0). The vaccine was well tolerated, and adverse events were balanced between the groups. The most frequent adverse events were tachypnoea (n=86 in the LAIV group and n=54 in the placebo group), cough (n=73 and n=43), and runny nose (n=68 and n=39), most of which were mild. Interpretation: This single-dose Russian-backbone LAIV was safe and efficacious at preventing symptomatic laboratory-confirmed influenza illness due to vaccine-matched strains. LAIV programmes might reduce the burden of influenza illness in Bangladesh. Funding: The Bill & Melinda Gates Foundation.